First record of Chromatomyia periclymeni (Hendel, 1922) (Diptera: Agromyzidae) for Belarus - Volosach, Marina V. (Experimental Biology and Biotechnology, 2019)
This paper presents the first finding of mining fly Chromatomyia periclymeni (Hendel, 1922) (Diptera: Agromyzidae) for Belarus (two sites in Minsk). Collecting of snowberry leaf blades damaged by Ch. periclymeni larvae was carried out by the author during the field seasons of 2017–2018. Based on literature data for adjacent regions, it can be assumed that Ch. periclymeni is a locally distributed, alien for the fauna of Belarus species of Agromyzidae.